Laminated rustproof film
By adopting a multi-layer structure anti-rust film, high-density polyethylene and low-density polyethylene combined with calcium nitrate particles and amine/amine salts, the problem of poor rust protection effect of the existing anti-rust film under high-temperature long-term storage conditions is solved, and the long-term rust protection effect in high-temperature environments is achieved.
Patent Information
- Application Number
- JP2023144634
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
The existing anti-rust film cannot effectively provide rust protection under high-temperature long-term storage conditions, and the rust protection effect is insufficient in high-temperature environments.
A multi-layer anti-rust film consisting of high-density polyethylene and low-density polyethylene is used, which contains calcium nitrate particles with an average particle size of 50 μm or more, and amine/amine salts are added to some layers.
This rust-resistant film can maintain good rust protection under high-temperature long-term storage conditions, ensuring that metal products are protected from rust for a long time during transportation and storage, and providing sufficient rust protection under high-temperature environments.
Smart Images

Figure 2025037612000001 
Figure 2025037612000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated rust-preventive film. [Background technology]
[0002] As described in the examples of Patent Document 1, a laminated rust-preventive film having a resin layer made of low-density polyethylene containing sodium nitrite is known. The laminated rust-preventive film according to the present invention exhibits rust-preventive effects regardless of the storage conditions after production and before use. The examples are based on the premise that the laminated rust-preventive film is used in the state immediately after production. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-131267 A Summary of the Invention [Problem to be solved by the invention]
[0004] It is possible to achieve a longer-term rust prevention effect by adopting a two-layer laminated sheet as a laminated rust prevention film for storing metal products, etc. However, in recent years, there has been a growing demand for a film that does not lose its properties as a rust prevention film even when stored for a long period of time at high temperatures, and that exhibits the same rust prevention properties as under normal conditions in situations where rust prevention is required even in harsh environments or situations where it is difficult to handle with care, and where rust prevention is required for a long period of time. In such a case, conventional anti-rust films have been unable to provide sufficient anti-rust properties. [Means for solving the problem]
[0005] As a result of extensive investigations aimed at solving the above problems, the present inventors have found that the problems can be solved by the following means, and have thus completed the present invention. 1. A laminated rust-preventive film having the following resin layer 1 and resin layer 2: Resin layer 1: calcium nitrite particles having an average particle size of 50 μm or more and a density of 0.945 g / cm 3 Layer containing high density polyethylene Resin layer 2: Layer containing low-density polyethylene and / or linear low-density polyethylene 2. A laminated rust-preventive film according to 1, which has the following resin layer 3 on the resin layer 2 side. Resin layer 3: A layer containing calcium nitrite particles having an average particle size of 50 μm or more, and low-density polyethylene and / or linear low-density polyethylene. 3. The laminated rust-preventive film according to 1 or 2, wherein the resin layer 2 contains an amine / ammonium salt. 4. The laminated rust-preventive film according to any one of 1 to 3, wherein the thickness of the resin layer 1 is 15 to 45 when the thickness of the laminated rust-preventive film is taken as 100. Effect of the Invention
[0006] According to the laminated rust-preventive film containing calcium nitrite salt having a specific particle size of the present invention, a container, sheet-like object, or bag-like object at least partly composed of this laminated rust-preventive film can maintain its rust-preventive effect for a longer period of time by storing products such as metal products that may rust or by being packaged together with the products, and therefore can reliably prevent rust from occurring for a longer period of time when the metal products are transported, stored, etc. Furthermore, even if the storage conditions before use are high temperatures, the laminated rust-preventive film has excellent rust prevention properties when in use, and can exhibit sufficient rust prevention properties even under harsh usage environments. Specifically, the laminated rust-preventive film can exhibit good rust prevention properties in the VIA test after fatigue testing and in the air. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention relates to a laminated rust-preventive film, and this laminated rust-preventive film may have a substrate layer. The present invention will be described below. In the present invention, the density of the resin was measured according to the method specified in Method A of JIS K7112:1999. In this specification, calcium nitrite, potassium nitrite, and sodium nitrite may be referred to as Ca nitrite, K nitrite, and Na nitrite, respectively. Furthermore, in the present invention, each of the resin layer 1, the resin layer 2 and the resin layer 3 may consist of one layer or multiple layers.
[0008] (Laminated anti-rust film) The laminated rust-preventive film of the present invention is a laminated rust-preventive film having a resin layer 1 and a resin layer 2. However, the resin layer 1 may be provided in a plurality of layers, and the resin layer 2 may be provided in a plurality of layers. When the resin layer 1 is composed of two or more layers, the calcium nitrite and resin contained in each layer can be determined independently. Each of these layers must satisfy the requirements for the laminated rust-preventive film of the present invention. When the resin layer 2 is composed of two or more layers, the low-density polyethylene and / or linear low-density polyethylene contained in each layer can be determined independently. Each of these layers must satisfy the requirements for the laminated rust-preventive film of the present invention.
[0009] [Resin layer 1] The resin layer 1 is made of calcium nitrite particles having an average particle size of 50 μm or more and a density of 0.945 g / cm 3 The resin layer 1 may be formed from a single layer, or a plurality of resin layers 1 may be laminated to form the resin layer 1 as a whole. When a plurality of resin layers 1 are laminated, each resin layer 1 is independently set to have an average particle size and content of calcium nitrite particles contained therein, and a density of 0.945 g / cm or less. 3 The type of high density polyethylene and the resin composition can be determined as above. From the viewpoint of mechanical strength and processability, the melt flow rate value (MFR) is preferably 1.0 g / 10 min or more, more preferably 3.0 g / 10 min or more, and even more preferably 4.0 g / 10 min or more. Also, it is preferably 10.0 g / 10 min or less, more preferably 8.0 g / 10 min or less, and even more preferably 7.0 g / 10 min or less. By setting it in this range, it has an appropriate strength and a suitable viscosity during melt processing, so that it is possible to include and coat particulate calcium nitrite in the resin, and it is possible to prevent the rust inhibitor from falling off from the resin molded body.
[0010] (Calcium nitrite particles having an average particle size of 50 μm or more contained in resin layer 1) The resin layer 1 contains calcium nitrite particles having an average particle size of 50 μm or more. The content of the calcium nitrite particles is preferably 0.01 parts by weight or more, more preferably 0.10 parts by weight or more, even more preferably 0.50 parts by weight or more, and most preferably 1.00 parts by weight or more, per 100 parts by weight of the resin layer 1. The content is preferably 10.00 parts by weight or less, more preferably 5.00 parts by weight or less, even more preferably 3.00 parts by weight or less, and most preferably 2.50 parts by weight or less. If the content is less than 0.01 parts by weight, it is difficult to further improve the rust prevention properties, and if it exceeds 10.00 parts by weight, molding processing becomes difficult. The average particle size of the calcium nitrite particles is 50 μm or more, preferably 55 μm or more, and more preferably 60 μm or more. The average particle size is preferably 150 μm or less, and more preferably 140 μm or less. When the average particle size is 50 μm or more, excellent effects are exhibited in the VIA test after the fatigue test. It is preferable not to contain potassium salt, sodium salt or magnesium salt of nitrite, but these may be contained without limiting the average particle size as long as the effect of the present invention is not impaired. The content of these metal nitrite salts when contained is preferably, for example, 0.01 part by weight or more and preferably 1.0 part by weight or less in 100 parts by weight of the resin layer contained. If it exceeds 1.0 part by weight, molding becomes difficult.
[0011] The average particle size of the calcium nitrite particles is the value of the major axis D50 of the calcium nitrite particles before they are incorporated into the resin layer. In the present invention, calcium nitrite particles are used, and a resin having a density of 0.945 g / cm 3 By using a combination of the above high-density polyethylenes, the decrease in the amount of calcium nitrite was suppressed even after storage for 288 hours in an atmosphere of 60°C, and the product retained the same rust-preventing properties as a new product. In contrast, calcium nitrite particles with a D50 of 50 μm or more and a density of 0.945 g / cm 3 When the calcium nitrite was dispersed in polyethylene of less than 100 g / kg, the amount of calcium nitrite decreased after storage at 60°C for 288 hours. Furthermore, calcium nitrite particles with a D50 of less than 50 μm and a density of 0.945 g / cm 3 When dispersed in the above high density polyethylene, the amount of calcium nitrite decreased after storage in an atmosphere of 60°C for 288 hours.
[0012] (Resin Constituting Resin Layer 1) The resin constituting the resin layer 1 has a density of 0.945 g / cm 3 It is necessary that the material contains high density polyethylene with a density of 0.945g / cm3 or more. 3 The high density polyethylene is not limited, and may be any known polyethylene selected from the polyethylenes listed below in [Polyethylenes that can be used in resin layer 1 and resin layer 2]. 3 If the above conditions are met, excellent effects are exhibited in the VIA test following the fatigue test. In addition, the density of 100 parts by weight of the resin constituting the resin layer 1 is 0.945 g / cm 3 The content of the high density polyethylene is more than 50 parts by weight. It is preferably 70 parts by weight or more, more preferably 90 parts by weight or more, and even more preferably 95 parts by weight or more. The density is 0.945 g / cm 3 By using the above-mentioned high density polyethylene, the effect of calcium nitrite as a rust inhibitor can be maintained for a long period of time during use. As a resin other than the high density polyethylene, other polyolefins such as polyethylene that can be used in combination may be contained. Even when other polyolefins such as polyethylene that can be used in combination are contained, the density of the entire resin constituting the resin layer 1 is 0.945 g / cm 3 That's all. By combining with calcium nitrite particles having the above average particle size, the thermal loss of calcium nitrite can be suppressed. Furthermore, by reducing the thickness of the resin layer 1 in the entire laminated rust-preventive film in combination with the high deliquescent property of calcium nitrite, the volatility of the rust inhibitor derived from calcium nitrite can be increased even in a high humidity atmosphere. Density 0.945g / cm 3 Among the above high density polyethylenes, 0.948g / cm 3 More than 0.950g / cm is preferable. 3 The above is more preferable.
[0013] [Resin layer 2] (Resin Constituting Resin Layer 2) The resin constituting the resin layer 2 may contain low-density polyethylene and / or linear low-density polyethylene. Here, the low-density polyethylene and / or linear low-density polyethylene has a density of 0.925 g / cm 3 The following are preferred. Such low-density polyethylene and / or linear low-density polyethylene is not limited, and known polyethylenes can be used from those described in the following [Polyethylenes that can be used in resin layer 1 and resin layer 2]. The density is 0.925 g / cm 3 When the thickness is equal to or less than this, in combination with the resin layer 1, an excellent effect is exhibited in the VIA test after the fatigue test. In addition, the density of 100 parts by weight of the resin constituting the resin layer 2 is 0.925 g / cm 3The content of the low density polyethylene and / or linear low density polyethylene described below is more than 50 parts by weight. It is preferably 55 parts by weight or more, more preferably 60 parts by weight or more, and even more preferably 65 parts by weight or more. As a resin other than the low density polyethylene and / or linear low density polyethylene, other polyolefins such as polyethylene that can be used in combination may be contained. In addition, they may not be contained. Even when other polyolefins such as polyethylene that can be used in combination are contained, the density of the entire resin components constituting the resin layer 2 is 0.925 g / cm. 3 The following is preferred:
[0014] From the viewpoint of mechanical strength and processability, the melt flow rate value (MFR) is preferably 0.5 g / 10 min or more, more preferably 0.8 g / 10 min or more, and even more preferably 1.0 g / 10 min or more. Also, it is preferably 6.0 g / 10 min or less, more preferably 4.0 g / 10 min or less, and even more preferably 3.0 g / 10 min or less. By setting it in this range, in combination with the resin layer 1, it has an appropriate strength while having an appropriate viscosity during melt processing, thereby improving moldability. Density 0.925g / cm 3 Among the following low density polyethylenes and / or linear low density polyethylenes, 0.923 g / cm 3 The following is more preferable: 0.921 g / cm 3 The following are more preferred:
[0015] [Polyethylene that can be used in resin layer 1 and resin layer 2] The resin constituting the resin layer 1 has a density of 0.945 g / cm 3 The above-mentioned high density polyethylene, and the low density polyethylene and / or linear low density polyethylene which are the resins constituting the resin layer 2 can be selected from the following polyethylene polymers taking into consideration the requirements stipulated in the present invention. Resin layer 1 has a density of 0.945 g / cm 3 By using the above high density polyethylene in combination with a specific calcium nitrite, sufficient rust prevention properties can be achieved even in the VIA test after the fatigue test. By using low-density polyethylene and / or linear low-density polyethylene in the resin layer 2, heat sealing can be smoothly carried out when a bag-shaped product is produced with the resin layer 2 on the inside.
[0016] As such polyethylene, one or more types selected from polyethylene-based polymers, that is, homopolymers of ethylene, and copolymers using ethylene and an olefin other than ethylene as a monomer, can be used. Examples of olefins (olefin monomers) other than ethylene that constitute this polyethylene polymer include propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc. Thus, examples of polyolefin polymers include ethylene polymers, propylene polymers, 1-butene polymers, 1-hexene polymers, 4-methyl-1-pentene polymers, etc.
[0017] These polyethylene polymers may be used alone or in combination of two or more. That is, the polyolefin polymer may be a mixture of various polymers. When it is a mixture, it is sufficient that the mixture as a whole has a predetermined density. Among the above, the ethylene-based polymer includes ethylene homopolymer (polyethylene) and copolymer of ethylene and other monomer (ethylene copolymer). Examples of the ethylene homopolymer include low-density polyethylene (LDPE), linear low-density polyethylene (L-LDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). Specific examples of polyethylene polymers include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-pentene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, and ethylene-4-methyl-1-pentene copolymers. The ethylene units (structural units derived from ethylene) contained in the polyethylene polymer may account for more than 50% of the total number of structural units (usually 99.999% or less), but can account for, for example, 80 to 99.999% of the total number of structural units, or 90 to 99.995%, or even 99.0 to 99.990%.
[0018] [Other Resins That May Be Used in Combination with Resin Layer 1 and Resin Layer 2] As described above, in each of the resin layers 1 and 2, in addition to the polyethylene polymer that is essential for the resin layers 1 and 2, other polyethylene may be used in combination, or may not be used in combination. Such polyethylene can be arbitrarily selected from those listed above. Furthermore, resins other than polyethylene may be blended within the range that does not impair the effects of the present invention. Also, it is not necessary to blend any resins other than polyethylene.
[0019] The density of polyolefin resin is 0.880 to 0.945 g / cm3 from the viewpoint of processability. 3 From the viewpoint of mechanical strength and processability, the melt flow rate (MFR) is preferably in the range of 1.0 to 10.0 g / 10 min, and by having an appropriate viscosity during melt processing, it becomes possible to include and coat particulate calcium nitrite in the resin, and it becomes possible to prevent the rust inhibitor from falling off from the resin molded body.
[0020] [Amine / Ammonium Salts] An amine / ammonium salt (amine salt and / or ammonium salt) can be blended into the resin layer 2 in the present invention. Examples of such amine / ammonium salt include amine / ammonium salts of carboxylic acid, amine / ammonium salts of carbonic acid or nitrous acid, and the like, which are used as rust inhibitors. If necessary, an amine / ammonium salt may be blended into the resin layer 1. Alternatively, it is not necessary to blend such a salt. When the resin layer 2 contains an amine / ammonium salt, the content of the amine / ammonium salt in 100 parts by weight of the resin layer 2 containing the amine / ammonium salt is preferably 0.10 parts by weight or more, more preferably 0.20 parts by weight or more, and preferably 0.30 parts by weight or more, and is preferably 10.0 parts by weight or less, more preferably 5.0 parts by weight or less, even more preferably 3.0 parts by weight or less, and most preferably 1.5 parts by weight or less. When the resin layer 2 contains an amine / ammonium salt, the content of the amine / ammonium salt in 100 parts by weight of the entire laminated rust-proofing film (the entire film including the resin layer 3 when the resin layer 3 described below is used) is preferably 0.05 parts by weight or more, more preferably 0.10 parts by weight or more, and preferably 0.15 parts by weight or more. Also, it is preferably 5.0 parts by weight or less, more preferably 3.0 parts by weight or less, even more preferably 2.0 parts by weight or less, and most preferably 1.0 parts by weight or less.
[0021] (Amine Carboxylate) As the amine carboxylate, a salt formed by bonding cyclohexylamine, diisopropylamine, or dicyclohexylamine to the same carboxylic acid as the carboxylic acid component constituting the ammonium carboxylate can be selected.
[0022] (ammonium carboxylate) The ammonium carboxylate may be either an aliphatic ammonium carboxylate or an aromatic ammonium carboxylate. Specific examples of ammonium carboxylates include butyric acid, isobutyric acid, methacrylic acid, valeric acid, caproic acid, caprylic acid, capric acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, sorbic acid, oleic acid, oleic acid, isohexanoic acid, 2-methylpentanoic acid, 2-ethylbutanoic acid, isoheptanoic acid, isooctanoic acid, 2-ethylhexanoic acid, isononanoic acid, isodecanoic acid, 2-propylheptanoic acid, isoundecanoic acid, and isododecanoic acid. Examples of the ammonium salts include ammonium salts of aliphatic carboxylic acids such as ammonium salts of 2-butyloctanoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, and dodecanedioic acid, and ammonium salts of aromatic carboxylic acids such as benzoic acid, aminobenzoic acid, salicylic acid, p-tert-butylbenzoic acid, o-sulfobenzoic acid, 1-naphthoic acid, 2-naphthoic acid, phthalic acid, isophthalic acid, terephthalic acid, and cinnamic acid.
[0023] (amine / ammonium salts of carbonic acid and nitrite) In the above ammonium carboxylates and amine salts of carboxylic acids, those in which the carboxylic acid is replaced with carbonic acid or nitrous acid can be used. Among these, cyclohexylamine carbonate (CHC) is preferred.
[0024] The amine / ammonium salt is contained in the resin layer 1 and / or the resin layer 2 in the form of particles, and when the laminated rust-proofing film further comprises other resin layers, the amine / ammonium salt may or may not be contained in the other resin layers. The average particle size of the amine / ammonium salt is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more. Also, it is preferably 60 μm or less, more preferably 50 μm or less, and even more preferably 40 μm or less. This average particle size is the value of the major axis D50 of the particles of the ammonium salt of carboxylic acid or the like contained in the resin layer. By containing an amine salt or ammonium salt of a carboxylic acid or the like having this specific particle size and controlling the amount of rust-preventive gas generated, the rust-preventive effect can be stably maintained for a long period of time.
[0025] (Metal Carboxylate) A metal carboxylate may be independently contained in each of the resin layers 1 and 2 of the laminated rust-preventive film of the present invention. The metal carboxylate may be either an aliphatic metal carboxylate or an aromatic metal carboxylate. Examples of these metal salts of carboxylates include isobutyric acid, methacrylic acid, valeric acid, caproic acid, caprylic acid, capric acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, sorbic acid, oleic acid, oleic acid, isohexanoic acid, 2-methylpentanoic acid, 2-ethylbutanoic acid, isoheptanoic acid, isooctanoic acid, 2-ethylhexanoic acid, isononanoic acid, isodecanoic acid, 2-propylheptanoic acid, isoundecanoic acid, isododecanoic acid, 2-butyloctanoic acid, and shukumushi acid. One or more of the following can be used: aliphatic carboxylic acids such as benzoic acid, aminobenzoic acid, salicylic acid, p-tert-butylbenzoic acid, o-sulfobenzoic acid, 1-naphthoic acid, 2-naphthoic acid, phthalic acid, isophthalic acid, terephthalic acid, cinnamic acid, and the like; and metal salts such as sodium salts, potassium salts, calcium salts, and magnesium salts of aromatic carboxylic acids such as benzoic acid, aminobenzoic acid, salicylic acid, p-tert-butylbenzoic acid, o-sulfobenzoic acid, 1-naphthoic acid, 2-naphthoic acid, phthalic acid, isophthalic acid, terephthalic acid, and cinnamic acid.
[0026] When the resin layer 1 and the resin layer 2 each contain a metal carboxylate, the content of the metal carboxylate is preferably 0.001 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, per 100 parts by weight of the resin layer. If the content is less than 0.001 part by weight, it is difficult to achieve sufficient rust prevention, and if it exceeds 10 parts by weight, molding becomes difficult.
[0027] (Benzotriazole and tolyltriazole compounds) The resin layer 1 and the resin layer 2 of the laminated rust-preventive film of the present invention may each independently contain a benzotriazole-based compound and / or a tolyltriazole-based compound. Among them, one or more compounds selected from benzotriazole, 4-methylbenzotriazole, 5-methylbenzotriazole, etc. may be used. In addition, they may not be contained. The content of these benzotriazole-based compounds and tolyltriazole-based compounds is preferably 0.001 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, per 100 parts by weight of the resin layer contained therein. If the content is less than 0.001 part by weight, it is difficult to further improve the long-term rust prevention properties, and if it exceeds 10 parts by weight, molding processing becomes difficult.
[0028] Furthermore, within the scope of the present invention, known additives that are added to resins, such as antiblocking agents (AB agents), lubricants, antioxidants, antistatic agents, UV absorbers, and processability improvers, which are different from the above-mentioned additives, can be added to the resin layer 1 and the resin layer 2 independently, to the laminated rust-preventive film. Furthermore, even if an ionomer resin or a functional group-containing polyolefin resin is not blended into the laminated rust-preventive film for the purpose of retaining the rust inhibitor in the resin layer, the present invention can provide sufficient long-term rust prevention properties.
[0029] [Resin layer 3] A resin layer 3 can be provided on the surface of the resin layer 2 of the laminated rust-preventive film of the present invention. The resin layer 3 is a layer containing calcium nitrite particles having an average particle size of 50 μm or more, and low-density polyethylene and / or linear low-density polyethylene. The resin layer 3 contains calcium nitrite particles having an average particle size of 50 μm or more, which are used in the resin layer 1 as a rust inhibitor. As the low-density polyethylene and / or linear low-density polyethylene that can be used in the resin layer 3, it is preferable to use the low-density polyethylene and / or linear low-density polyethylene that can be used in the resin layer 2 described above. The calcium nitrite particles having an average particle size of 50 μm or more to be blended in the resin layer 3 can be selected from the range of calcium nitrite particles that can be contained in the resin layer 1 described above.
[0030] [Laminated anti-rust film] The laminated rust-preventive film of the present invention may have any structure, such as a laminated rust-preventive film having a substrate layer provided on only one side thereof, a laminated rust-preventive film having substrate layers provided on both sides thereof, a laminated rust-preventive film having a substrate layer laminated on both sides thereof, etc. Furthermore, any of the laminated rust-preventive films having any of these structures may be further laminated. The thickness of the resin layer 1 is preferably 15% or more and 45% or less of the total thickness of the laminated rust-proofing film of the present invention, regardless of the presence or absence of the resin layer 3. Similarly, the thickness of the resin layer 2 is preferably 55% or more and 85% or less. Furthermore, the resin layer 1 is preferably 20 to 50 μm, and the resin layer 2 is preferably 50 to 95 μm. When the resin layer 3 is provided, the resin layer 3 is preferably 10 to 30 μm. The laminated rust-preventive film of the present invention is basically formed by laminating a resin layer 1 and a resin layer 2. In addition to this, a resin layer 1, a resin layer 2 and a resin layer 3 may be laminated in this order. This resin layer 3 is a layer made of low-density polyethylene and / or linear low-density polyethylene, containing calcium nitrite particles having the same average particle size range as the calcium nitrite particles contained in resin layer 1, with an average particle size and content independent of those of resin layer 1. In this case, resin layer 3 preferably has a thickness of 5% to 25% of the total thickness of the laminated rust-preventive film consisting of resin layers 1 to 3.
[0031] (base material layer) A substrate layer can be provided on at least one surface of the laminated rust-preventive film of the present invention. The substrate layer is provided for the purpose of imparting strength to the laminated rust-preventive film of the present invention, imparting gas barrier properties and water vapor barrier properties, improving the tactile sensation and aesthetics, etc. As a material constituting the substrate layer, a material that does not inhibit the rust-preventive effect of the laminated rust-preventive film can be adopted, and it is preferable that the material is a material that has excellent adhesion to the resin constituting the laminated rust-preventive film. As materials for forming the substrate layer, resins that can be used in the above-mentioned laminated rust-preventive film, resins that have excellent adhesion to the laminated rust-preventive film, as well as woven fabric, nonwoven fabric, and paper can be used. When a resin is used, various known additives can be contained in the resin layer. The resin layer may be porous or non-porous. The method for forming the base layer from such a resin may be to form it simultaneously when forming the laminated rust-proofing film, or to form it separately from the laminated rust-proofing film and then laminate it by known means.
[0032] (Manufacture and use of laminated anti-corrosive films) The laminated rust-preventive film is formed by known means such as extrusion molding, inflation molding, vacuum molding, pressure molding, etc. Among them, it is preferable to obtain it by inflation molding. Based on the laminated rust-preventive film, it can have any shape such as a film, a sheet-like object, a bag-like object, a laminated sheet-like object, a tube-like object, or a box-like object. When a base film is laminated on the laminated rust-preventive film, the surface of the laminated rust-preventive film may be positioned on the inside of a container or a packaging sheet, that is, on the side of an object to be stored or packaged and rust-prevented. By containing calcium nitrite particles having this specific particle size, the amount of rust-preventing gas generated can be controlled, and as a result, the rust-preventing effect can be stably maintained for a long period of time. Furthermore, by adopting multiple resin layers, moisture gradually penetrates from the outside air in contact with the surface of the resin layer 1 toward the inside, so the rust-preventive gas is also generated little by little. Therefore, even without adding rust-preventive release agents such as carboxylic acid-modified polyolefin polymers, waxes, nonionic surfactants, and inorganic porous bodies, a high rust-preventive effect can be maintained more stably for a long period of time. Note that rust-preventive release agents such as carboxylic acid-modified polyolefin polymers, waxes, nonionic surfactants, and inorganic porous bodies may be added. Furthermore, the objects to be rust-proofed include a wide range of objects such as cast iron. EXAMPLES
[0033] The present invention will be described more specifically with reference to the following examples and comparative examples. It should be noted that the examples show one embodiment of the present invention and the present invention is not limited thereto. The density and MFR of each resin constituting each resin layer in the table are as follows: Resin HDPE has a density of 0.951g / cm 3 , MFR is 5.5g / 10min Resin HDPE2 has a density of 0.964g / cm 3 , MFR is 5.2g / 10min Resin HDPE3 has a density of 0.938g / cm 3 , MFR is 0.2g / 10min The density of LDPE resin is 0.920g / cm 3 , MFR is 2.0g / 10min The density of LLDPE resin is 0.903g / cm 3 , MFR is 3.8g / 10min Also, CHC is cyclohexylamine carbonate.
[0034] The materials were mixed by hand blending to prepare molding compounds for the laminated rust-preventive films of the Examples and Comparative Examples shown in the table. These compounds were then extruded into tubular laminated films using an inflation extrusion molding machine. Calcium nitrite (Ca nitrite), sodium nitrite (Na nitrite), and potassium nitrite (K nitrite) were obtained by crushing and classifying commercially available substances under arbitrary conditions.
[0035] Test method for VIA after fatigue test (performed in accordance with MIL-STD-3010C 5.4.1) (Fatigue Test) A laminated rust-preventive film measuring 8 inches in length and 2 inches in width was placed vertically in a beaker. This beaker was left to stand for 288 hours in a space with a temperature of 60°C and a humidity of 50%, in accordance with the MIL-STD-3010C5.4.1 standard. After standing, two laminated rust-preventive films measuring 6 inches in length and 1 inch in width were obtained from one laminated rust-preventive film measuring 8 inches in length and 2 inches in width.
[0036] (VIA test method after fatigue test) An SAE1018 plate with a diameter of 15.9 mm and a height of 12.7 mm was prepared, and the surface of the SAE1018 plate was polished by rubbing it left and right with #240. It was then polished by rubbing it up and down with #400. The polished surface was washed with first-class methanol and wiped with a professional wipe. The VIA test after the fatigue test was carried out in accordance with the US MILITARY STANDARD MIL-STD-3010C 5.4.1. Note that SAE1018 was used instead of SAE1010 in MIL-STD-3010C 5.4.1.
[0037] (Surface evaluation of VIA test results after fatigue test) Each test surface (the circular surface of the SAE1018 plate with a diameter of 15.9 mm) was inspected under 10x magnification. Each test surface was rated based on the number of corrosion spots found. Additionally, each test surface was magnified 40x to check for the presence or absence of spots greater than 300 μm in diameter. (Evaluation Criteria) ○: 3 or less spots and no spots with a diameter of more than 300 μm (compliant) △: Four or more spots or spots with a diameter of more than 300 μm (non-compliant) ×: Overall rust (not suitable)
[0038] [Space Test] The following test specimens were hung with nylon fishing line within a frame measuring 100 mm length x 100 mm width x 150 mm height, and the frame was gusset-sealed with the prepared film. After this test form was placed in the test environment described below for a specified period of time, the state of rust on the surface was evaluated based on the rust prevention evaluation criteria described below.
[0039] (Test piece) Cast iron (JIS G 5501) Size: φ30mm x 8mm
[0040] (Test environment) 25℃, 70%RH: 4 hours 50℃, 95%RH: 4 hours Set travel time: 2 hours, total 12 hours / 1 cycle evaluation Number of days: 7 days (14 cycles)
[0041] (Rust prevention evaluation criteria for spatial testing) 〇: No rust or discoloration △: Rust spots, slight discoloration ×: Rust or discoloration occurs on less than 10% of the test piece area.
[0042] [Table 1]
[0043] [Table 2]
[0044] In each of the Examples, the results of the VIA test after the fatigue test were good, whereas in each of the Comparative Examples, the results of the VIA test after the fatigue test were unsatisfactory. The results of the 7-day spatial test were △ in Examples 1 to 3. In contrast, the results of the 7-day spatial test were ◯ in Examples 4 to 19 in which the resin layer 2 contained an amine / ammonium salt. Comparative Examples 1, 2 and 6 are examples in which the resin layer 1 contains sodium nitrite or potassium nitrite. Although both are nitrites rather than Ca, when Na salt or K salt was used, the results of the VIA test after the fatigue test were inferior to those of the Examples. In particular, Comparative Examples 1 and 2, which have a resin layer 2 that does not contain a rust inhibitor, also showed inferior results in the spatial test. Comparative Examples 3 to 5 are examples in which the average particle size of Ca nitrite contained in the resin layer 1 is less than 50 μm. In these cases as well, the results of the VIA test after the fatigue test were poor. In Comparative Example 7, the density of the high-density polyethylene is 0.938 g / cm 3 This is an example that does not satisfy the density range of the present invention. In this case, the result of the VIA test after the fatigue test was insufficient. Comparative Example 8 is an example in which Ca nitrite was not contained in resin layer 1, and ammonium adipate, a rust inhibitor, was contained in resin layer 2. Comparative Example 9 is an example in which Ca nitrite was contained in resin layer 2, and ammonium adipate was contained in resin layer 1. In these cases, the results of the VIA test and the spatial test after the fatigue test were poor.
Claims
1. A laminated rust-preventive film having the following resin layer 1 and resin layer 2. Resin layer 1: calcium nitrite particles having an average particle diameter of 50 μm or more and a density of 0.945 g / cm 3 Layer containing high density polyethylene Resin layer 2: Layer containing low-density polyethylene and / or linear low-density polyethylene
2. 2. The laminated rust-preventive film according to claim 1, further comprising the following resin layer 3 on the resin layer 2 side: Resin layer 3: A layer containing calcium nitrite particles having an average particle size of 50 μm or more, and low-density polyethylene and / or linear low-density polyethylene.
3. 3. The laminated rust-preventive film according to claim 1, wherein the resin layer 2 contains an amine / ammonium salt.
4. 3. The laminated rust-preventive film according to claim 1, wherein the thickness of the resin layer 1 is 15 to 45 mm when the thickness of the laminated rust-preventive film is taken as 100 mm.
Citation Information
Patent Citations
Rust prevention film for package made of metal material
JP2019131267A